Dispenser Otomatis Berbasis Arduino Uno - Muh. Ilcardi Ralda; La Ode Ahmad Barata; Nanang Endriatno (Piston: Jurnal Teknologi, 2022)
Dispensers have an important role in providing adequate drinking water for needs and can be placed around where we work. The purpose of this research is how to design and make an automatic dispenser system based on Arduino Uno and it can work well when filling the glass when the glass is placed. This research was conducted by coding using Arduino IDE 1.0.6 software to program Arduino Uno to control servo motors and ultrasonic sensors. The results of this study indicate that the automatic dispenser can work to fill glasses from a distance of 5 cm to 0 cm and open the dispenser faucet 1 cm. From the manufacture of this tool it can be concluded that this tool works well, in accordance with its purpose to make it easier to take water, the automatic dispenser is driven by a servo motor with a wire attached to the side of the dispenser lever, the control system uses Arduino Uno. Suggestions can be given so that this tool can be developed. Another suggestion for development is that so that the automatic system of this tool can work properly, the placement of the sensor must be in the right position so that the glass plate can be filled properly, it is better to turn on the Arduino uno by using a switch.